Establishment of the Idea of Educational Ideal in Ukrainian Pedagogical Theory in XI –XIII Century - Yershova, Liudmyla (Pedagogical Discourse, 2013)
The article presents the results of the analysis of literary sources of XI–XIII centuries in which the educational ideal is presented as a dynamic category, sensitive to personal, social and historical factors, as the result of unique synthesis of religious, politica land cultural life of the society. The article also reveals the importance of the factors of a booker’s belonging to a certain Kniazhyi court and ideological specificity of his religious environment. It was defined that understanding of life goal depended on the «earth» or «celestial» dominants in the system of value orientations of a certain booker, causing specific orientation of the formulated educational ideals (an ascetic hermit, an active ascetic, a wise kniaz-ruler, an active Christian layman, a good woman). The article shows the basic content transformations ofthe educationalideal: the transition from radical to moderate asceticism; replacement of the cult of strength and courage to the prevalence of faith and wisdom; correction of the idea that kniaz was chosen by God as anecessity for spiritual power to control secular power, etc. Common features in the creative heritage of Middle Age sthinkers are humanism, democracy, nationality and patriotism of the created educational ideals, to which, as to the classics, Ukrainian intellectuals of the future will refer.